(untitled) - Kowalski, Dean A. (Boston, Mass., 2005)
This new text/reader is the first major introduction to philosophy that incorporates movies as a key pedagogical element. Throughout the text, summaries of and references to current and classic films engage students, revealing what they already know and addressing issues that they find relevant. The book highlights the major topics within philosophy and includes the core readings that represent them; instructors with various pedagogical approaches will find
Keywords: Philosophy,Philosophy in motion pictures; Introductions